Beyond organisational borders: The soft power of innovation in the health sector; comment on what managers find important for implementation of innovations in the healthcare sector – Practice through six management perspectives - Costa, C. M. (International Journal of Health Policy and Management, 2022)
Health is not just a physiological state, it is also a relational phenomenon. This means health is a collective challenge, often a cross-border one. Diplomacy in the health sector has progressively received more attention from formal actors (national states, international organisations, etc) but after the coronavirus disease 2019 (COVID-19) challenge, this attention became a global emergency mobilising an expansive set of knowledge-seeking players (industry, research networks, civil society, etc). This paper comments on and leverages the contribution by Palm and Feschier on innovation management at the organisational level to address a complementary dimension: the internationalization process, and the need for a particular set of skills and routines to make innovations travel through different markets and regulatory contexts. Our argument is that marketing (knowing about customers) and diplomacy (understanding framing institutions) constitute a set of dynamic capabilities (soft power) that are critical for the effective internationalization of innovation.